Systemic-to-pulmonary collateral flow associations with antegrade pulmonary flow in single ventricle patients: insights from cardiac magnetic resonance imaging - Yanovskiy, Anna; Martelius, Laura; Nyman, Nicolina; Vepsäläinen, Teemu; Mattila, Ilkka; Rahkonen, Otto; Ojala, Tiina (Frontiers in Cardiovascular Medicine, 2024)
Purpose: In the palliated single ventricle anomalies, a considerable amount of the aortic flow may be absorbed by the systemic-pulmonary collateral flow (SPCF), which can be noninvasively assessed by cardiac magnetic resonance (CMR). The aims of this study were to 1) identify factors associated with SCPF in pediatric single ventricle patients, and 2) establish a cutoff values indicating an association between SCPF and a reduction in antegrade pulmonary flow. Methods: A retrospective single-tertiary-center cohort study included 158 consecutive CMR studies of patients with a single ventricle. In the uni-and multivariable analysis, SPCF was presented as a percentage of the total pulmonary venous flow (SPCF%PV). The minimal clinically important difference in QP/QS ratios was estimated as ≥ 0.50, and an optimal cutoff value was defined using the receiver operating characteristic (ROC) curve. Results: SPCF%PV was significantly smaller in the post-total cavopulmonary connection (TCPC) group than in the pre-TCPC patients (p<0.001). The patient's higher age and a higher antegrade pulmonary flow were associated with a lower SPCF%PV. A negative weak association was observed between the SPCF%PV and systemic saturation (r= -0.39, p<0.001). SPCF%PV did not associate with ventricular volumes nor ejection fraction. The SPCF%PV was significantly smaller in patients that were palliated primarily with a pulmonary artery banding compared to those palliated with a BT-shunt (p=0.002) or RV-PA-shunt (p=0.044). In the ROC analysis, for pre-TCPC patient's, a cutoff of SPCF%PV 42% yielded a sensitivity of 100% and specificity of 80% for significantly reduced antegrade pulmonary flow (AUC 0.97). In the post-TCPC group, the optimal SPCF%PV cutoff was 34% (sensitivity 100%, specificity 98%, AUC 0.99). Conclusion: SPCF results in a considerable left-to-right shunt, which subsequently diminishes spontaneously after TCPC. Our findings indicated that for pre-TCPC patients, an SPCF%PV threshold of 42% (sensitivity 100%, specificity 80%), and for the post-TCPC group, a threshold of 34% (sensitivity 100%, specificity 98%) were effective in identifying reduced antegrade pulmonary flow.